Construction of RC frame / Mohammad Huzairi Mohd Husni - Mohd Husni, Mohammad Huzairi (Universiti Teknologi Mara, Perak, 2018)
An opportunity has been given to fulfil the internship program at Faridaz Development Sdn Bhd. Faridaz Development is the company that is known as the main contractor especially in property developer and renovation work. The company develop the property according to the client’s demand in various specification. As the trainee of the company. I was assigned in team project which supervise the construction progress of the company project. The supervisor need to ensure the project’s method statement and specification of the material is according to the agreement. Also on the supervising of the progress and reporting to the company for claim work. For the first task, I was assigned to supervise the remedial work at the client property that had been hack due to crack caused by surrounding vibration and minor settlement. The location of the property is surrounded by heavy machinery such as piling driving work. The vibration on surrounding effect the house and cause crack. The task is to ensure the labour remedy the crack with the correct procedure and method with the correct material. As for other, the problem that had been recognized during internship program had been analyzed and had been come out with the recommendation to overcome the problem before getting severe.